1992
DOI: 10.1128/mcb.12.8.3390
|View full text |Cite
|
Sign up to set email alerts
|

The coat protein of the yeast double-stranded RNA virus L-A attaches covalently to the cap structure of eukaryotic mRNA.

Abstract: The eukaryotic mRNA 5' cap structure m7GpppX (where X is any nucleotide) interacts with a number of cellular proteins. Several of these proteins were studied in mammalian, yeast, and drosophila cells and found to be involved in translation initiation. Here we describe a novel cap-binding protein, the coat protein of L-A, a double-stranded RNA virus that is persistently maintained in many Saccharomyces cerevisiae strains. The results also suggest that the coat protein of a related double-stranded RNA virus (L-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 33 publications
2
44
0
1
Order By: Relevance
“…4B). Decapping activity has also been demonstrated in Gag of L-BC virus (14). Therefore, it is likely that the cap-snatching mechanism of L-A virus is widespread among totiviruses of fungi.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…4B). Decapping activity has also been demonstrated in Gag of L-BC virus (14). Therefore, it is likely that the cap-snatching mechanism of L-A virus is widespread among totiviruses of fungi.…”
Section: Discussionmentioning
confidence: 96%
“…Thus M1 can be maintained in the cell without the helper virus provided that L-A proteins are expressed from a vector (13). Two decades ago Blanc et al (14) found that the L-A coat protein Gag covalently binds the cap structure of mRNA. The reaction was inhibited by the cap analogue m 7 GpppG but not by the nonmethylated GpppG.…”
mentioning
confidence: 99%
“…The double-stranded L-A virus, which infects yeast, employs a novel mechanism to decap cellular messages. The GAG capsid protein forms a covalent linkage to the RNA cap, promoting cap removal (37,38). Because L-A transcripts are not capped, the destabilized cellular RNA transcripts are thought to saturate the degradation machinery, allowing a portion of the L-A transcripts to escape degradation by cellular factors.…”
Section: Discussionmentioning
confidence: 99%
“…Gag covalently binds cap structures in vivo. When purified L-A viral particles are incubated with RNA containing a cap structure in the presence of magnesium, the His-154 residue of the L-A Gag protein becomes covalently bound to the m 7 GMP cap, releasing the uncapped mRNA (3,4). Mutations converting this residue to Arg, Asn, or Ser result in Gag proteins that bind caps but do not become covalently attached.…”
Section: Ski2p Ski3p and Ski8p Repress Translation Of Capmentioning
confidence: 99%